Comparison of Herd Profile Among Different Types of Dairy Farms in Kerala - George, Sabin; Saseendran, P. C.; Anil, K. S.; Gleeja, V. L.; Pramod, S. (International Journal of Livestock Research, 2020)
The present study was conducted in five districts representing different agro- climatic zones in Kerala, in order to assess the herd profile of dairy farmers. The average herd size based on standard animal units were 3.13 ± 0.08, 9.52 ± 0.3 and 36.38 ± 3.65, in small, medium and large farms respectively. Irrespective of farm size the preferred mode of replacement was purchase of animals. Own finance was the dominant source of money for animal purchase in all types of farms. Subsidy linked purchase was 20.6, 20.0 and 9.3 per cent in small, medium and large farms respectively. Majority of animals purchased in all farms were lactating animals. In small and medium farms majority of the animals belonged to the production level of 10-15 litres/day. Crossbred Holstein Friesian animals were more likely to be purchased by farmers irrespective of the size of farm. The proportion of pregnant animals was 27.44, 24.43 and 24.60 respectively in small, medium and large farms. Results showed that the average age of heifers were 20.49 months and 32.07 per cent heifers were pregnant. Irrespective of farm size majority of both male and female calves were below six months of age.